Isolations and Identification of bacteria present in the fluids Save contact lenses used by some students girls of the Tikrit University - Shaymaa Naji Daham; Hayfaa Rajab Alwan; Hind Tariq Hamed (Tikrit Journal of Pure Science)
The number of people who wear contact lenses (CLS) has been especially increased in the past decade as an alternative to glasses, but many of them do not realize the extent of the hazards involved, and these risks Keratitis associated with microbial causes, so this study included isolation and identification the bacteria in fluids save to  lenses with 42 users of contact lenses of students in inner section in the Tikrit University. The study showed the presence of different bacterial groups in the fluids keeping contact lenses which included Staph. epidermis with percentage 30.30% and Staph. Aureuswith percentage 21.21% and the bacteria Streptococcus pneumonia  precentage 18.18% and also was diagnosed with Pseudomonas aeruginosa and with 9.09%, while the intestinal bacteria Serratia odorfera where it was obtained with 6.06%. As for the sensitivity of the bacterial isolates to antibiotics, the study proved that more antibiotic effect on gram positive and negative bacteria is erythromycin followed by chloramphenicol while more antibiotic resistance by bacteria is ezithromycin, due to the erroneous and excessive use of these drugs by people.